Analysis of Work Environment and Stress Management on Work Productivity - Nasution, Dony Orlando; Salman, Radian; Winarsi, Sri (Universitas Pamulang, 2023)
This study aims to determine the effect of the work environment and stress at work on employees' work productivity in a company. Illustrate for the community in general and the company, and several factors can cause the increase and decrease in work productivity. This study uses quantitative research with exploratory, descriptive data presentation by taking a sample at a university in East Java. With multiple linear regression techniques can be seen the relationship that occurs to these problems. The results of this study indicate that the Work Environment (X1) and Stress at Work (X2) influence Work Productivity (Y). This research also includes suggestions for improvement to increase work productivity